Oxygen oxidation of ethylbenzene over manganese porphyrin is promoted by the axial nitrogen coordination in powdered chitosan. Issue 54 (17th May 2016) - Huang, Guan; Yuan, Ru Xun; Peng, Yan; Chen, Xiang Feng; Zhao, Shu Kai; Wei, Su Juan; Guo, Wen Xin; Chen, Xi
Abstract : A less wasteful production method of oxidation ethylbenzene to acetophenone and phenethyl alcohol was adviced. It revealed an important role in tuning catalytic reactivity of metalloporphyrins by the axial ligand for oxidation of hydrocarbon. Abstract : To understand the role of a cysteinate axial ligand in cytochrome P450 enzyme activity and to explore the actions of the axial ligand in a biomimetic catalyst, tetrakis(4-carboxyphenyl)porphyrin manganese chloride (Mn TCPP) was acylated and ligated onto powdered chitosan (pd-CTS). The grafted material was used as a catalyst for the oxidation of ethylbenzene with molecular oxygen. Common spectroscopic techniques, in particular X-ray photoelectron spectroscopy, were used to characterize the grafted material. We found that the coordination of chitosan to manganese porphyrin changed the electron cloud densities of the manganese ion in the catalytic center. This promoted cleavage of the Mn–Cl bond in the Mn TCPP/pd-CTS, it tripled the catalytic activity of manganese tetrakis(4-carboxyphenyl)porphyrin and the catalytic efficiency of the metalloporphyrin. The catalyst decreased the environmental impact of the oxidation of ethylbenzene to acetophenone and phenethyl alcohol.